Growth of PB 260 Clone (Hevea brasiliensis (Willd. ex A. Juss.) Muell-Arg.) in Different Potting Media and Fertilization Scheme - Risal Ardika; Pearl B. Sanchez; Rodrigo B. Badayos; Pompe C. Sta Cruz (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2017)
Rubber is an important commodity for Indonesia. Currently, a problem encountered in the propagation of rubber planting materials is the availability of ideal soils with optimum nutrition as the planting medium. Peat can be used as a growing medium but it still has weaknesses such as high level of acidity and poor in nutrient content. This study was aimed to assess the performance of rubber budded stump grown on modified potting medium and applied with different forms and rates of fertilizers. The nursery experiment consisted of 17 treatments and arranged in a randomized complete block design. After rubber nursery stage, the performance of the rubber budded stump were also monitored in the field for 10 months. Results showed that mixture of peat and soil with the application of recommended rate of solid or liquid fertilizer produced rubber budded stump with bigger stem diameter and taller plants. The potting medium stimulated early root development which led to higher nutrient uptake. These budded stump also performed better in field, showed higher leaf nutrient concentration after 6 months and produced bigger stem diameter after 10 months.